Risk governance: examining its impact upon bank performance and risk-taking - Gontarek, Walter; Belghitar, Yacine (Wiley, 2018)
As policy-makers in the United States contemplate a relaxation of financial regulation, our study contributes to this dialogue by testing the veracity of heightened standards of risk governance activities for US bank holding companies (BHCs). Our study examines evidence relating to the adoption of these standards by BHCs following regulatory intervention. We find that board-level risk appetite practices have a profound association upon BHC performance and tail risk. Our estimates show that BHCs which adopt risk appetite practices exhibit a significant improvement in headline performance and reduced tail risk measures. Our research is relevant to academics by identifying the significance of this risk governance practice which has been introduced by global regulators. For practitioners (including board members, risk managers, policy-makers and regulators), our study validates the efficacy of risk appetite frameworks as the future shape of financial regulation is being actively debated in the US.
Keywords: Risk governance; risk appetite; BHCs; financial institutions; boards of directors; bank regulation